Bacteriophage Typing of Salmonellae. II. New Bacteriophage Typing Scheme - Ibrahim, Abdelaziz E. (1969)
A phage-typing technique for salmonellae is described. One battery of phages was used to type three serotypes of Salmonella, namely, S. typhimurium, S.typhimurium var. copenhagen, and S. heidelberg. In all, 443 S. heidelberg cultures were typed into 22 phage types, 185 S. typhimurium cultures into 35 phage type, and 92 S. typhimurium var. copenhagen cultures into 26 phage types. The stability of the phage types was established by retyping 168 cultures belonging to all three serotypes. The epidemiological significance of the phage types demonstrated was evaluated by comparing phage types obtained from the University of Minnesota and those from the National Animal Disease Laboratory. Further investigation of the S. heidelberg phage types has shown that the cultures represented repeated isolates from the same birds or from a group of birds in the same flock.